Prevalence and infestation dynamics of intestinal protozoa infections (cryptosporidiosis, giardiasis and eimeriosis) among calves in dairy farms of Kazakhstan - Ussenbayev, Altay; Kurenkeyeva, Dariyash; Aydin, Ali; Sakhariya, Laura; Ruzmatov, Saidulla (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigates the epidemiological characteristics of significant gastrointestinal protozoa diseases among calves, including cryptosporidiosis, giardiasis, and eimeriosis, in Kazakhstan.MethodsUsing cross-sectional surveys and laboratory diagnostics we examined the age and seasonal dynamics of intestinal parasitic infestations in calves, specifically focusing on Giardia spp., Cryptosporidium spp., and Eimeria spp. For this purpose, samples of feces were individually collected from 1,586 calves of varying ages and breeds in 12 industrialized farms from 11 districts of Akmola and Northern Kazakhstan Regions. Parasites were identified using Fuelleborn, Heine and ZnSO4 flotation microscopic techniques. Calves were categorized into four age groups (1–30, 31–90, 91–120, and >120 days) to evaluate the prevalence and age- associated risk of infection with above parasite species, and their combinations. Logistic regression was performed to estimate odds ratios (ORs) and 95% confidence intervals (CIs), using calves aged 1-30 days as the reference group. To examine the effects of age and time of year on the likelihood of parasitic infection ANOVA and a generalized additive logistic model (GAM) were used. It was found that in all investigated farms the age significantly influences the likelihood of infection with each parasite.Results and discussionCryptosporidium spp. infections were highly concentrated in the youngest calves, with prevalence 49.2% detected in the 1-30-day group. The risk of infection dropped dramatically with older age (p < 0.001). Prevalence Eimeria spp. in the 1-month group was 2.0% and significantly increased with age. Calves aged 31-90 days had 27.3 times higher odds of infection (95% CI: 17.07–45.35, p < 0.001), with elevated odds persisting in older groups (p < 0.001). 5.2% of the youngest calves were infected with Giardia spp., and the species was more evenly distributed across age groups, with no statistically significant variation. No significant seasonal variation in infection rates was found. These findings suggest that at the conditions of intensive dairy farming in central and northern Kazakhstan the age-targeted parasite control strategies may be more effective than seasonal approaches for managing parasitic infections' control in calves.